Changing practice: assessing attitudes toward a NICE-informed collaborative treatment pathway for bipolar disorder. Issue 2 (8th March 2021) - Elliott, Adele Louise; Watson, Stuart; Dodgson, Guy; Cohen-Tovée, Esther; Ling, Jonathan
Abstract : Background: Bipolar disorder is a chronic mental health condition, which can result in functional impairment despite medication. A large evidence base supports use of psychological therapies and structured care in the treatment of mood disorders, but these are rarely implemented. e-Pathways are digital structures that inform and record patient progress through a healthcare system, although these have not yet been used for bipolar disorder. Aims: To assess the perceived benefits and costs associated with implementing a collaborative NICE-informed e-pathway for bipolar disorder. Method: Healthcare professionals and people with bipolar disorder attended a workshop to share feedback on e-pathways. Data were collected through questionnaires ( n = 26) and transcription of a focus group, analysed qualitatively by a framework analysis. Results: Patients and healthcare professionals welcomed the development of an e-pathway for bipolar disorder. There were five elements to the framework: quality and delivery of care, patient–clinician collaboration, flexibility and adaptability, impact on staff and impact on healthcare services. Conclusions: Identification of benefits and costs ensures that future development of e-pathways addresses concerns of healthcare professionals and people with bipolar disorder, which would be essential for successful implementation. Recommendations for this development include making e-pathways less complicated for patients, ensuring sufficient training and ensuring clinicians do not feel their skills become invalidated. Limitations of the study, and directions for future research, are discussed.